KAJIAN PENGELOLAAN AIR IRIGASI BENDUNG PIJENAN - Umar, Fauzan; Legono, Djoko; Nurrochmad, Fatchan (Civil Engineering Forum Teknik Sipil, 2007)
Bantul Regency is about 506.85 km2 consists of 16,440 ha paddy fields and 34,245 ha upland fields. The Pijenan weir is one of weirs located in Bedog river in Bantul Regency. The weir provides irrigation water for Jigutan command area (Pijenan Upstream) of 2.074 ha. Kebonongan command area was previously irrigated from Kamijoro free intake in Progo River. The Kamijoro free intake did not properly function properly due to the sediment deposited in 1969. This condition requires supply taken from Pijenan weir. Irrigation water supply taken to Kebonangan command area can be carried out if irrigation water to Jigutan command area has been optimum. Optimally utilized irrigation water for Jigutan command area is necessary based on the crop pattern and crop variety in order to maximize the farmers’ profit. Based on the restitution of irrigation management policy, farmers free to decide which crop variety will be cultivated in accordance to paddy-paddy-palawija pattern. Paddy as the main crop and palawija (corns, beans, peanuts, onion, and chilly) can be cultivated anytime in order to gain the maximum profit based on the available water in Jigutan command area. The optimization analysis of irrigation water allocation for Jigutan command area was performed using the linear program. Water allocation for Jigutan command area of 100% and 50% of available water resulted in optimum cultivation area of 822.88 ha with profit of Rp 7.688.517.507,00 and 612.88 ha with profit of Rp 6.743.877.335,00. The crop intensity with water allocation of 100% and 50% was 278% (197% paddy and 81% palawija) and 207.05% (114.05 paddy and 93% palawija), respectively. These results described that the optimum area of paddy crop cultivation is significantly sensitive to irrigation water allocation compared to the palawija market price. This explains why the profit obtained by the farmers is dependent from the palawija variety. Results of the optimization of irrigation water allocation of 100% and 50% of the available water to Jigutan command area provides annual supply to Kebonongan command area for 155.233.586 m3 and 75.316.444 m3, respectively.